(untitled) (Research, Society and Development, 2021)
Introduction: Concomitantly with the mechanical and technological advance, contemporary society shows an emergence of sedentary aspects and a preference for high-calorie diets that together favor the installation of obesity and decline in physical fitness, especially in school-age children and adolescents. Objective: To evaluate and verify the effect of body adiposity on physical fitness related to the health of public school students. Method: The sample consisted of 363 students of both sexes, aged between 9 and 17 years old, selected voluntarily in schools in the municipality of Votuporanga/SP. All volunteers were found to be anthropometric assessments: weight, height and skin folds (tricipital and calf); and motor tests defined as physical resources: flexibility (FLEX), localized muscle resistance (RML) and cardiorespiratory fitness (ApC). Subsequently, the Body Mass Index (BMI) and fat percentage (%F) were calculated. To analyze the data used in the statistical software SPSS 22.0, adopting a significance of p>0.05. Results: There were negative correlations between %F and physical resources FLEX (r=-0.147; p=0.045) and RML (r=-0.328; p=0.000) in girls, and RML (r=-0.330; p=0.000) and ApC (r=-0.475; p=0.000) in boys. Conclusion: The higher the %F, the lower the performance of students in motor tests regarding the studied physical capacities, therefore, obesity in these individuals is characterized as a preponderant factor to low physical fitness, which, in turn, can favor the emergence of comorbidities, impairing the processes human development and early adulthood.